Enhancing Communication Skills through Translanguaging in Pesantren-Based English Club - Alifatul Umniyah; Setiawan, Slamet; Adi Nugroho, Him’mawan (Institut Agama Islam Negeri Madura, 2025)
Translanguaging has become a significant concept in multilingual education, particularly in pesantren-based schools where students frequently use multiple languages, including Indonesian, English, Arabic and local languages. This study aims to explore how translanguaging is practiced by students in English Club activities and its effectiveness as a tool for enhancing communication. Using a qualitative approach, data were collected through observations, interviews, and audio recordings of students engaged in English Club activities at pesantren-based school. The findings reveal that translanguaging is a flexible and dynamic practice, enabling students to naturally mix languages to comprehend complex ideas, express emotions and build confidence. It also fosters active participation, creativity, and collaboration, helping students effectively navigate academic and personal discussions. This study draws on Vogel and Garcia’s (2017) theory, which emphasizes the use of students’ full linguistic repertoire, and Cenoz and Gorter’s (2017) distinctions between planned and spontaneous translanguaging. The results confirm these theories and extend their application to the pesantren context, illustrating how translanguaging enhances communication, supports collaborative learning, and promotes cultural understanding. Practical recommendations are provided for educators to integrate translanguaging into teaching strategies, creating an effective learning environment for multilingual students.